Arylaminopropanone Derivatives as Potential Cholinesterase Inhibitors: Synthesis, Docking Study and Biological Evaluation - Hudcová, Anna; Kroutil, Aleš; Kubínová, Renata; Garro, Adriana D; Gutierrez, Lucas J; Enriz, Daniel; Oravec, Michal; Csöllei, Jozef (Molecules (Basel, Switzerland), 2020)
Neurodegenerative diseases in which the decrease of the acetylcholine is observed are growing worldwide. In the present study, a series of new arylaminopropanone derivatives with N-phenylcarbamate moiety (1-16) were prepared as potential acetylcholinesterase and butyrylcholinesterase inhibitors. In vitro enzyme assays were performed; the results are expressed as a percentage of inhibition and the IC50 values. The inhibitory activities were compared with reference drugs galantamine and rivastigmine showing piperidine derivatives (1-3) as the most potent. A possible mechanism of action for these compounds was determined from a molecular modelling study by using combined techniques of docking, molecular dynamics simulations and quantum mechanics calculations.
Keywords: aktivace enzymů; Molecular Dynamics Simulation; molecular modelling; molekulární konformace; Enzyme Activation; propanolaminy; enzyme assays; simulace molekulového dockingu; vazba proteinů; Molecular Structure; Structure-Activity Relationship; Propanolamines; lidé; acetylcholinesterase; simulace molekulární dynamiky; Molecular Conformation; N-phenylcarbamate; Models, Molecular; molekulární struktura; molekulární modely; vztahy mezi strukturou a aktivitou; butyrylcholinesterase; cholinesterasové inhibitory; Cholinesterase Inhibitors; arylaminopropanone; Protein Binding; Molecular Docking Simulation; Humans